Rebel Rose - Theriault, Emma (Los Angeles : Disney-Hyperion, 2020)
Continues the story of Belle and Adam, once known as the Beast, who, soon after their marriage, must take on heavy responsibilities as rulers of Aveyon during the French Revolution.
Keywords: Kings and rulers -- Juvenile fiction; Revolutions -- Juvenile fiction; Magic -- Juvenile fiction; Social classes -- Juvenile fiction; Beauty and the beast (Tale) -- Adaptations; Fairy tales -- Adaptations; Kings, queens, rulers, etc -- Fiction; Revolutions -- Fiction; Magic -- Fiction; Social classes -- Fiction; Beauty and the beast (Tale) -- Adaptations; Fairy tales; France -- Juvenile fiction -- History -- Revolution, 1789-1799; France -- Fiction -- History -- Revolution, 1789-1799; Historical fiction; Adaptations